PERCEPTUAL QUALITY OF GEOMETRICALLY DISTORTED IMAGES PART II: HUMAN PERCEPTION OF THE QUALITY OF GEOMETRICALLY DISTORTED IMAGES - Iwan Setyawan (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2010)
This paper presents a study of how human perceive the quality of geometrically distorted images by presenting the design and analysis of a subjective-test experiment. The results of this experiment is then used to evaluate the performance HPQM (Homogeneity-based Perceptual Quality Measurement) method presented in the first paper of this series.